ASUHAN KEPERAWATAN PADA NY. T (P5A0) DENGANPOST SECTIO CAESAREA DI WILAYAH SENTUL JAWA BARAT - Anindita Ariani Nursuyanto (2023)
Background: Sectio Caesarea is a way of giving birth to a fetus by making an incision in the uterine wall through the front wall of the abdomen. Mothers giving birth by Caesarean section will feel some discomfort, namely severe pain. The recovery process tends to last longer than normal delivery. SC action will disrupt continuity or tissue connection because the incision will release pain receptors, causing the patient to experience pain after the anesthetic effect wears off. The purpose of this research is to carry out nursing care for clients who experience post section caesarean section with impaired physical mobility in the Sentul area, West Java. Method: The research design used is a descriptive method in the form of a case study in implementing nursing care. The study was taken in the Sentul area, West Java involving 1 client with a post-section caesarean diagnosis with impaired mobility problems. The results of the study: Obtained the results of research on clients with a post-section caesarean diagnosis, a priority diagnosis was obtained, namely in the form of impaired physical mobility associated with anxiety. After 3 days of nursing care, it was found that the client was able to carry out normal activities. Conclusion: It is expected that from the case of Mrs. T with patients with post-section caesarean is a partially resolved problem. The suggestion from this researcher is to follow and understand the education provided and increase knowledge about maternal health post section caesarean section.